Phytochemical Analysis of Some Wild Vegetables from Thane Dist, Maharashtra, India - R D Taware; B K Avchar (The Bioscan, 2025)
Indian traditional knowledge about the wild edible plants (WEPs) is most important part for the sustainable development. People are addicted to eat hybrid food for the last few decades. This study focuses on the preliminary survey and phytochemical analysis of certain wild edible plants providing valuable insights into their potential benefits. Hibiscus sabdariffa, Cassia tora, Amaranthus cruentus (Red leaves), Amaranthus viridis (Green leaves), Holarrhena spp., these WEPs are tested for analysis of Phytochemicals. During the last few years, several studies have focused on the chemical characterization and the bioactivities of various WEPs, while numerous ethno pharmacological studies have highlighted their contemporary uses in modern dietsand their positive health effects. The results revealed the presence of medicinally active compounds in those five plants. From the phytochemical analysis, it could be seen that Phenolic, Flavonoids and Antioxidant Properties i.e. 2-diphenyl-1-picrylhydrazyl (DPPH) were present in all the plants. Flavonoids were absent only from Holarrhena spp. Some plant species are used for nutritional purposes and for enhancing overall health. These WEPs are utilized by tribal communities to effective treatment and manage a variety of diseases and health conditions, including diabetes, malaria, jaundice, stomach disorders, coughs, piles, amebic stool, gastritis, arthritis, and cysts, as well as to promote blood purification. However, these vegetables are growing in wild conditions and have very good nutritional and medicinal properties; they need to be domesticated by proper techniques providing agro climatic practices.